Development and Validation of a Fecal Extraction Procedure for the Assessment of Multiple Fecal Biomarkers of Intestinal Inflammation (P13-025-19). (13th June 2019) - Lewis, Erin; Guo, Weimin; Li, Lijun; Wu, Dayong; Combs, Gerald; Meydani, Simin
Abstract: Objectives: Fecal biomarkers have emerged as an important tool to assess intestinal inflammation and permeability. Commonly measured biomarkers include calprotectin (CP), myeloperoxidase (MPO), alpha-1-antitrypsin (AAT) and neopterin (NEO). We sought to develop a simple, fast and cost-effective single extraction procedure for use in determining all four biomarkers of interest. The applicability and sensitivity of this procedure for use in healthy adults was examined. Methods: Sample extraction buffers and methods including sample weight, dilution, homogenization and centrifugation were all considered in the development of a single extraction procedure. An extraction buffer that included phosphate-buffered saline, phenylmethylsulfonyl fluoride, bovine serum albumin and Tween 20 was used to extract fecal samples. To assess the applicability and sensitivity of the single extraction procedure, concentrations of CP, MPO, AAT and NEO were measured using commercially available sandwich ELISA kits, according to manufacturer's instructions. Results: CP, MPO and AAT concentrations were measured in fecal samples of healthy adults (aged 50–80 years, n  = 85) and found to be comparable to findings of previously published studies in healthy populations. Mean concentrations of CP and AAT were 3.6 ± 3.8 µg/g of wet weight (range 0.14–18.0 µg/g) and 2.3 ± 0.73 µg/g (range 0.76–5.2 µg/g), respectively. Mean fecal MPO concentrations were 135 ± 24 ng/g (range 3–1290 ng/g). NEO concentrations were examined in a subset of healthy adults ( n  = 10), with mean concentrations of 18 ± 1 ng/g (range 17–20 ng/g). Conclusions: We demonstrated the efficacy of a single extraction procedure used to assess multiple fecal biomarkers of intestinal inflammation. This simple, fast and inexpensive extraction method will facilitate the determination of multiple fecal biomarkers which is critical in validating their use as clinical or predictive biomarkers of intestinal inflammation. Funding Sources: Supported by the U.S. Department of Agriculture – Agricultural Research Service (ARS), under Agreement No. 58–1950-4–003, the Bill & Melinda Gates Foundation and Canadian Institutes of Health Research Postdoctoral Fellowship.